Musculoskeletal disorders and quality of life among undergraduate health sciences students: a cross-sectional study / Nur Syafiqah Adilla Kamalruzaman, Tengku Adilah Tengku Sabri and Siti Nor Ismalina Isa - Kamalruzaman, Nur Syafiqah Adilla; Tengku Sabri, Tengku Adilah; Isa, Siti Nor Ismalina (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Musculoskeletal disorders (MSD) can deteriorate individuals' physical and mental health, thereby lowering their quality of life (QOL). The current study aim was to determine the relationship between MSD and socio-demographic characteristics with QOL among undergraduate health sciences students. A cross-sectional study was conducted by selecting 330 health sciences students in Universiti Teknologi MARA (UiTM) Puncak Alam. Nordic Musculoskeletal Questionnaire and WHOQOL-BREF questionnaires were used as research instruments. A total of 86.6% of the students had experience MSD at least in one body region, with the lower back being the most common site (63.3%). The Environmental domain of QOL scored the highest (M=68.16, SD=17.82), while the Psychological domain was the lowest (M=52.84, SD=12.66). Hips or thigh pain reported significantly lower scores in the Psychological domain only. Older age reported significantly lower score in the Physical, Psychological and Environmental domains. Higher body mass index (BMI) showed significantly lower scores in the Physical and Environmental domains. In contrast, those students who had a clinical training experience showed significantly higher scores in the Physical and Psychological domains. Hips or thigh showed an impact on QOL especially psychologically. The findings from this study can be used as a baseline for future research on the relationship between MSD and QOL, particularly among young adults